0214 Simulating Responsibility Increases Final Year Medical Student Ward Attendance. (1st November 2014) - Cullum, Robert; Theobald, Hannah; Wright, Adam; Voll, Jessika
Abstract : Background: There is currently little research into methods to improve ward attendance by medical students, or the impact it might have on examination performance and clinical ability. Existing work has found correlation between attendance and improved examination scores. 1 There are also decreasing opportunities for students to be involved in technical skills, with significant variation in what they have seen and done at graduation; 2 so attendance is key. Methodology: We studied 20 final year Medical Students from the University of Nottingham undertaking placements in Medicine or Surgery at Nottingham University Hospitals NHS Trust. Students had volunteered to act as a mentor for a work experience programme organised by a student group (WAMS Nottingham). We surveyed the Medical Students after the week to see whether they had spent more time on the wards as a consequence of the programme and reasons for this. Results: Students reported spending a mean of 4.50 h on the wards normally, with this increasing by 1.90 to 6.40 when they had a work-experience student shadowing them (p = 0.003). They reported the main reasons for this as responsibility to their mentee, to practice teaching and their own interest. Conclusions: In spite of a small sample size and notable potential for bias, this report does provide a potential solution to improving the attendance behaviour of final year medical students: by giving them a task to simulate responsibility for example of a Foundation Year doctor. References: Deane RP, Murphy DJ. Student attendance and academic performance in undergraduate obstetrics/gynecology clinical rotations. Journal of the American Medical Association, (2013) 310(21), 2282-2288. Doi: 10.1001/jama.2013.282228. Accessed 02/08/2014 Boots RJ, et al . They just don't get enough! Variable intern experience in bedside procedural skills. Internal medicine journal, (2009). 39 (4), 222-227. Doi:10.1111/j.1445-5994.2009.01699.x, Accessed 02/08/2014